The game of models: Dietary reconstruction in human evolution. Issue 174 (January 2023) - Paine, Oliver C.C.; Daegling, David J.
Abstract: Despite substantial additions to the paleontological record and unanticipated improvements in analytical techniques since the Journal of Human Evolution was first published, consensus on the diet of early hominin species remains elusive. For instance, the notable advances in the analyses of hominin dental microwear and stable isotopes have provided a plethora of data that have in some instances clouded what was once ostensibly a clear picture of dietary differentiation between and within hominin taxa. In the present study, we explore the reasons why the retrodiction of diet in human evolution has proven vexing over the last half century from the perspective of both ecological and functional-mechanical models. Such models continue to be indispensable for paleobiological reconstructions, but they often contain rigid or unstated assumptions about how primary paleontological data, such as fossils and their geological and taphonomic contexts, allow unambiguous insight into the evolutionary processes that produced them. In theoretical discussions of paleobiology, it has long been recognized that a mapping function of morphology to adaptation is not one-to-one, in the sense that a particular trait cannot necessarily be attributed to a specific selective pressure and/or behavior. This article explores how the intrinsic variability within biological systems has often been underappreciated in paleoanthropological research. For instance, to claim that derived anatomical traits represent adaptations related to stereotypical behaviors largely ignores the importance of biological roles (i.e., how anatomical traits function in the environment), a concept that depends on behavioral flexibility for its potency. Similarly, in the paleoecological context, the underrepresentation of variability within the 'edible landscapes' our hominin ancestors occupied has inhibited an adequate appreciation of early hominin dietary flexibility. Incorporating the reality of variation at organismal and ecological scales makes the practice of paleobiological reconstruction more challenging, but in return, allows for a better appreciation of the evolutionary possibilities that were open to early hominins.